Peningkatan Kapasitas Kelompok PKK Melalui Pelatihan Produk Olahan Ubi Jalar Ungu di Desa Bangbayang, Kabupaten Cianjur - Hamidatun, Hamidatun; Pujilestari, Shanti; Widiati, Euis (Abdi Masyarakat, 2022)
Bangbayang Village, Gekbrong District, Cianjur is an area with the main agricultural commodities being rice and purple sweet potato. This program aimed to increase knowledge and ability of PKK group in the Bangbayang Village in processing purple sweet potato into chips and cakes. The method used in this activity were an analysis of PKK group condition, training on food production and packaging labels, as well as evaluation of knowledge and attitudes. Based on the activities carried out, several benefits were obtained for partners including increasing knowledge about food production based on purple sweet potato and packaging labels, increasing partner attitudes and increasing partner capabilities in manufacturing chips and cakes of purple sweet potato products.In addition, based on the evaluation of the usefulness of the program, most of the participants agree to make the product as an alternative for new business ideas.